Clinical Characteristics of HIV Patients Presenting with Weight Loss: A Cross-Sectional Study: Clinical Characteristics of HIV Patients Presenting with Weight Loss - Ali, Ahmad; Badshah, Salim; Ikramullah, Qazi; Ullah, Naveed; Ullah, Shahid; Obaidullah, . (Pakistan Journal of Health Sciences, 2025)
Recognizing the epidemiology of human immunodeficiency virus (HIV) infection is essential for managing HIV infection. Research on the nutritional health of patients infected with HIV has revealed significant weight loss during the course of the infection, and this occurrence is frequently viewed as a negative indicator of survival prognosis. Over 26 million individuals with HIV are currently undergoing antiretroviral therapy (ART), which has greatly lessened the impact of HIV disease. Objectives: To determine the frequency of human immunodeficiency virus in patients presenting with weight loss at Lady Reading Hospital, Peshawar. Methods: This observational cross-sectional study was conducted at the Department of General Medicine, Lady Reading Hospital, Peshawar, from 1st July 2022 to 1st January 2023. 117 patients of both genders with weight loss were included in this study. Every patient was tested for HIV through an initial screening test. Patients with positive status on initial screening tests were referred to the special testing clinic for further confirmation. Human immunodeficiency virus was noted. Results: The mean age was 41.5±7.8 years and the age range in this study was from 25 to 60 years. Males were 69.2% and females were 30.8%. Human immunodeficiency virus (HIV) was positive in 7.7% of patients. HIV had a significant association with family socioeconomic status, with a p-value of 0.00. Conclusion: In conclusion this study demonstrates that HIV is associated with weight loss and wasting remains a highly prevalent complication in the modern antiretroviral era.